Climate-Smart Agriculture extension services manual for Parnassus in Jamaica. - Campbell, Donovan; Tomlinson, Jhannel; Eitzinger, Anton; Lizarazo, Miguel; Buckland, Sarah (National Irrigation Commission Ltd. Ministry of Agriculture and Fisheries.(Jamaica), 2022)
This Climate-Smart Agriculture extension services manual for Parnassus has been prepared as an output for the 'Capacity Building Program to Improve Stakeholder Resilience and Adaptation to Climate Change in Jamaica' project. It aims to provide agricultural extension staff in the region with ready-to-use guidelines for climate-smart practices, and incorporates the local experiences of farmers as well as the expertise of local and international adaptation researchers.